How can conditional cash transfers diminish crime? An application of Travis Hirschi’s social control theory - Breckin, Edmund (Crime prevention and community safety, 2019)
Recent literature has taken an interest in the potential of conditional cash transfer (CCT) poverty reduction programmes to alleviate crime. Whilst literature continues to grow, results have been inconsistent with variations in the impact recorded. Although the literature has continued to debate if a relationship exists between CCTs and crime, it fails to demonstrate how these programmes might impact crime. Utilising social control theory, the paper demonstrates how CCT programmes can facilitate crime reduction by strengthening social bonds. Drawing on the research, evidence is examined for each social bond, thus demonstrating the potential for CCTs to diminish crime. This paper concludes that further research is needed to give credence to the application of social control theory but by applying the theory to CCTs it offers the first theoretical understanding of relationships between CCTs and crime.